Learning motivation and student achievement : description analysis and relationships both - Riswanto, Ari; Aryani, Sri (COUNS-EDU: The International Journal of Counseling and Education, 2017)
Education is very important for humans, through the education throughout the world will increasingly flourish. However, if faced with the activities within the learning process, not a few men (students) who have less motivation in learning activities. This resulted in fewer maximal learning processes and in turn will affect student achievement. This study focuses to discuss matters relating to the motivation to learn and student achievement, with the aim of strengthening the importance of motivation in the learning process so that a clear relationship with student achievement. The method used is descriptive analysis and simple correlation to the 97 students taking the course introduction to Microeconomics and Indonesian. The conclusion from this research is the students have a good record if it has a well and motivated as well, and this study concludes their tie's difference between learning motivation and achievement of students on two different courses.